A New Simulator for Dynamic Local Grid Refinement for Reservoir Simulation - Al-Sabeeh, Ahmed N. Nimir (Basrah Journal for Engineering Sciences, 2009)
The ability to predict the performance of a petroleum reservoir is of immense importance for the petroleum industry. Numerical simulation is the most powerful tool that can be used for reservoir performance prediction. In the current study a new simulator has been designed for two phase compressible oil water flow through compressible porous media. The new simulator is able to treat the frontal advancement and the high rate of change region by static and dynamic local grid refinement. A new approach is proposed in this study to trace the frontal advancement. The proposed simulator has been applied to several field reservoir cases and show good performance.